Strategies for teaching vocabulary to foster english fluency in 7° grade students at Basica General Santo Tomas, in 2016 - Atencio Villarreal, Gladys Esther (David, Panamá : UDELAS, 2016)
The aim of this work is based on the research of possible strategies that could be used to teach vocabulary.
GENERAL INDEX Dedicatory Acknowledgement General Index Graphic Index Explanation Introduction CHAPTER II: ANTECEDENTS AND STATEMENT OF THE PROBLEM CHAPTER II : THEORETICAL FRAMEWORK 2.1. Concepts 2.1.1. Vocabulary 2.1.2. Strategy 2.1.3. Fluency 2.2. Characteristics of EFL Acquisition 2.2.1. Stages of secon language acquisition 2.3. Theories 2.3.1. Second language acquisition theory by Steven Krashen 2.3.2. Theory of syntax by Chomsky 2.3.3. Theory of social development by Lev Vygotsky 2.4. Strategies used to help students to gain vocabulary 2.4.1. With semantic field theory 2.4.2. By association 2.4.3. By using realia 2.4.4. By word in contexts 2.5. Ways of gaining vocabulary 2.5.1. By dictionaries 2.5.2. By teachers 2.6. Elements of learning vocabulary that must be considered in the teaching process 2.6.1. Principles of vocabulary instruction in a foreing language 2.6.2. Cognitive factors in second language learning 2.6.3. How words are remembered 2.7. Efectiveness and beneffits that the strategies for teaching vocabulary provides to the learners CHAPTER III: METHODOLOGICAL ASPECTS CHAPTER IV: ANALYSIS AND RESULTS Conclusions Recommendations Bibliography
Incluye General Index
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; ENGLISH -- TESIS DE LICENCIATURA -- STRATEGIES; ENGLISH -- TESIS DE LICENCIATURA -- TEACHING VOCABULARY; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; BÁSICA GENERAL SANTO TOMAS - CHIRIQUÍ - PANAMÁ